Banda Aceh mangrove vegetation structure in 2023 based on NDVI (Normalized Difference Vegetation Index) analysis - Musrina Putriani; Wira Dharma (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Mangroves are coastal forest ecosystems found in tropical and subtropical regions. such as the city of Banda Aceh. Based on their habitat, mangroves are a type of wetland forest that can store large amounts of carbon. The purpose of this study is to determine the structure of mangrove vegetation in the city of Banda Aceh through NDVI analysis. The analysis method used was NDVI and sample observation using plots. The results of the analysis show that the vegetation structure is directly proportional to the NDVI value. Areas with high NDVI values are dominated by tree, while areas with low NDVI values are dominated by seedling.Keywords:MangroveVegetationNDVI